Integrasi Sustainable Development Goals dalam Program Pesantren Ekologi: Perbedaan Sustainability Awareness pada Siswa SMA - Ratna Sari; Agung Purwanto; Muktiningsih Nurjayadi (WISE Pendidikan Indonesia, 2026)
Sustainability awareness is a key component of education for sustainable development, yet empirical evidence regarding students’ awareness in ecological boarding school programs remains limited. This study aimed to examine the level of Sustainable Development Goals (SDGs) integration in the Pesantren Ekologi program, assess students’ sustainability awareness (SA), and investigate differences in SA based on gender and grade level. A quantitative cross-sectional survey design was employed involving 406 senior high school students from West Java Province, Indonesia. Data were collected using Likert-scale questionnaires measuring SDGs integration and SA. The data were analyzed using descriptive statistics, independent samples t-test, and Welch ANOVA. The results indicated that SDGs integration within the Pesantren Ekologi program was perceived at a high level across cognitive, socio-emotional, and behavioral learning dimensions, while students’ SA was also generally high across environmental, social, and economic dimensions. Significant gender differences were found, with female students demonstrating higher SA than male students, although the effect size was small. In contrast, no significant differences were identified across grade levels. These findings suggest that SA is not necessarily associated with grade level alone and highlight the importance of contextual, participatory, and action-oriented learning experiences in sustainability education. The findings also support the implementation of SDG 4.7 by emphasizing the role of education in promoting sustainable development competencies. Future studies are recommended to employ longitudinal and mixed-methods approaches to better understand factors influencing students’ SA.